Living with Spirits and Environmental Conservation Efforts in Rural North-eastern Madagascar - Mölkänen, Jenni (Approaching religion, 2025)
Focusing on embodied and material aspects of lived religion in everyday practices, this article points to the need for culturally relevant concepts and practices to understand the everyday relations of the farmers under investigation with spirits. In north-eastern Madagascar, Marojejy National Park was established by transnational environmental organizations and multilateral development funders. To make the national park economically sustainable, rice and vanilla farmers living nearby have been recruited to ecotourism activities as guides, cooks and porters. The environments of rural farmers are inhabited by various spirits that demand people’s attention in their everyday life. For example, as discussed in this article, a piece of land can be evil, causing sickness to anyone who farms on it, or spirits at a particular tree can bring success to the people who ask for blessings from them. The embodied ability to act correctly in local ecologies informs the farmers’ long-term sustained presence in these places and environments. It is noted that in environmental conservation efforts, often based on secular worldviews, one should not dismiss religious experiences. Practices involving spirits and rituals, though often regarded as irrational, can have significant societal effects.